2019
DOI: 10.1002/pen.25213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clay amount and reprocessing cycles on thermal, morphological, and mechanical properties of polypropylene/organovermiculite nanocomposites

Abstract: Nanocomposites of polypropylene (PP) and PP-grafted-maleic anhydride (PP-g-MA) with and without organophilic vermiculite (OVMT) (5-8%w/w) were evaluated. The nanocomposites and neat PP were submitted to extrusion reprocessing cycles. It was found that the presence of OVMT in PP/PP-g-MA was critical for maintaining thermal stability during reprocessing. The exfoliation/intercalation was confirmed, mainly, in the nanocomposite submitted to reprocessing cycles, by X-ray diffraction. The melt flow index (MFI) valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The molecular weight drop during the reprocessing of PP can be also accounted for by an increase in the melt flow index with the reprocessing cycles. Figure 1 b shows that the values of MFR for PP increased as a function of the number of reprocessing cycles, indicative of the molecular weight loss of the polymer matrix during reprocessing [ 34 ]. Research findings have shown an inverse relation between MFR and apparent viscosity, which directly relates to chain length [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular weight drop during the reprocessing of PP can be also accounted for by an increase in the melt flow index with the reprocessing cycles. Figure 1 b shows that the values of MFR for PP increased as a function of the number of reprocessing cycles, indicative of the molecular weight loss of the polymer matrix during reprocessing [ 34 ]. Research findings have shown an inverse relation between MFR and apparent viscosity, which directly relates to chain length [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…number of reprocessing cycles, indicative of the molecular weight loss of the polymer matrix during reprocessing [34]. Research findings have shown an inverse relation between MFR and apparent viscosity, which directly relates to chain length [35].…”
Section: Effect Of Reprocessing Cyclesmentioning
confidence: 99%
“…The increment of the MFI means a drop in the melt viscosity and consequently a negative change in the plastic's molecular weight as confirmed by the work of Araújo et al 69 They reported a polymer viscosity decrease caused by a reduction in intermolecular interactions and entanglements which leads to reductions in molecular weight and the length of the polymer chain. The MFI for the virgin PP was provided by the datasheet of the PP manufacturer and the glass fiber-reinforced PP had an increase of 57% after passing through the screws of the extruder in 10 runs from the first run.…”
Section: Rheological Propertiesmentioning
confidence: 66%
“…[ 1,4‐8 ] The effects of different types of nanoclays on the crystallization temperature of PP composites have also been studied in detail. [ 9‐11 ] However, correlations of crystallization, recrystallization, and crystal growth mechanisms with the obtained thermomechanical properties of the polymer nanocomposite have been rarely discussed. A recent study showed that the HDT of a PP/LLDPE (linear low‐density polyethylene) blend decreases in the presence of talc.…”
Section: Introductionmentioning
confidence: 99%